It's fun to know why : experiments with things around us - Schwartz, Julius (New York : McGraw-Hill Book Company, Inc, 1952)
Through specific experiments the reader is led to discover scientific facts about such everyday materials as iron, salt, paper, and plastic.
Include index.
Keywords: Science -- Juvenile literature; Science -- Experiments